Analisis Permasalahan Pelaksanaan Sistem Penjaminan Mutu Internal (Studi Kasus di SMK Cor Jesu Malang) - Rosida Kerin Meirani; Ahmad Yusuf Sobri; Sunarni Sunarni (Kelola: Jurnal Manajemen Pendidikan, 2022)
This study aims to determine the problems in the implementation of the Internal Quality Assurance System (SPMI) at SMK Cor Jesu Malang. The areas of focus are the curriculum, facilities and infrastructure, and community relations. This study uses a descriptive qualitative approach with a case study design. Data were collected by interview, observation, and documentation methods. The data were analyzed by collecting, condensing, presenting data, and finally drawing conclusions. The validity of the data is checked by using triangulation of sources and methods. The result of the study is that the implementation of the internal quality assurance system has been going well, but there are problems in 3 areas, which include curriculum, infrastructure, and public relations. The problem in the curriculum field is that teachers who come from the industry do not yet have the pedagogic ability to develop learning tools. The problem in the field of infrastructure is the lack of staff to manage school facilities. The problem related to the field of public relations is public opinion which tends to assume that vocational graduates are no better than high school graduates.